2023
DOI: 10.3390/metabo13010102
|View full text |Cite
|
Sign up to set email alerts
|

PPAR Signaling Maintains Metabolic Homeostasis under Hypothermia in Freshwater Drum (Aplodinotus grunniens)

Abstract: Aplodinotus grunniens, known as freshwater drum, is a kind of eurythermal freshwater fish that is widely distributed in North America. In 2019, our research group reached a milestone on its artificial breeding and cultivation and have investigated its physiological adaption to the environment, providing a breakthrough and prospects for aquaculture. However, its adaptability and metabolic homeostasis to hypothermia is not fully understood. In this experiment, cold stress was conducted at 18 °C (LT18) and 10 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…FFA uptake, storage, and oxidation can also be regulated by binding to PPARs within the cell [33]. PPAR signaling also maintains lipid metabolic homeostasis during cold stress with reduced plasma glucose concentrations in fish [34].…”
Section: Discussionmentioning
confidence: 99%
“…FFA uptake, storage, and oxidation can also be regulated by binding to PPARs within the cell [33]. PPAR signaling also maintains lipid metabolic homeostasis during cold stress with reduced plasma glucose concentrations in fish [34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, animal saliva can affect the growth through the saliva-specific group. For example, the PPAR signaling pathway has been found to maintain lipid and amino acid metabolism homeostasis during cold stress [ 34 ]. Therefore, it can be speculated that animal saliva may maintain the growth of L. chinensis by maintaining cellular lipid and amino acid metabolism homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…As a regulator, PPAR controls the expression of a series of genes involved in lipid and lipoprotein metabolism [ 76 ]. In addition, our previous study found that PPAR signaling is implicated in the metabolic homeostasis of lipids and amino acids in freshwater drum with hypothermia [ 48 ]. PPARs are activated under starvation stress to regulate the expression of downstream adipose catabolism genes [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…In light of these prospects, we imported freshwater drum larvae and achieved a worldwide breakthrough in advanced research on artificial breeding, feeding, and domestication. In 2022, we achieved large-scale fry breeding, laying the groundwork for the industrialized development of freshwater drum culture and the breeding of new varieties [ 45 , 46 , 47 , 48 , 49 ]. However, in the practical aquaculture, we found freshwater drum was susceptive to lipid deposition in the liver, which adversely affected the health of the freshwater drum.…”
Section: Introductionmentioning
confidence: 99%